2016
DOI: 10.1111/cgf.12797
|View full text |Cite
|
Sign up to set email alerts
|

Partial Functional Correspondence

Abstract: In this paper, we propose a method for computing partial functional correspondence between non-rigid shapes. We use perturbation analysis to show how removal of shape parts changes the Laplace–Beltrami eigenfunctions, and exploit it as a prior on the spectral representation of the correspondence. Corresponding parts are optimization variables in our problem and are used to weight the functional correspondence; we are looking for the largest and most regular (in the Mumford–Shah sense) parts that minimize corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
209
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(213 citation statements)
references
References 34 publications
(58 reference statements)
2
209
0
Order By: Relevance
“…[KBBV15, PBB*13, RRBW*14, SK14, KBB*13, ERGB16]) and new consistent descriptors have been suggested [COC14, GSTOG16], these methods did not adjust the point‐wise recovery method. Recently, this framework was extended to computing partial correspondence [RCB*16, LRB*16, LRBB17], and to computing correspondences in shape collections [SBC14, HWG14, KGB16]. In addition, functional maps have been used for analysis and visualization of maps [OBCCG13, ROA*13], and image segmentation [WHG13].…”
Section: Related Workmentioning
confidence: 99%
“…[KBBV15, PBB*13, RRBW*14, SK14, KBB*13, ERGB16]) and new consistent descriptors have been suggested [COC14, GSTOG16], these methods did not adjust the point‐wise recovery method. Recently, this framework was extended to computing partial correspondence [RCB*16, LRB*16, LRBB17], and to computing correspondences in shape collections [SBC14, HWG14, KGB16]. In addition, functional maps have been used for analysis and visualization of maps [OBCCG13, ROA*13], and image segmentation [WHG13].…”
Section: Related Workmentioning
confidence: 99%
“…For domains with boundary Bohle & Pinkall [BP13] showed that prescribing binormal boundary conditions preserves the self‐adjointness and ellipticity of the extrinsic Dirac operator (see [CPS13, Section 6.3] for a discretization); a similar argument may be possible for the relative Dirac operator. However, the shape of the boundary can cause trouble in spectral geometry processing particularly in the case of partial matching of surface patches [RCB∗17]. Rather than trying to “cut” the meshes so that they all have identical boundary shape, or resorting to potentially fragile re‐discretization ( e.g ., [BSK05]), we substitute standard boundary conditions for an infinite potential well that provides consistent behavior across patches with different boundary shapes or discretizations.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…Another related set of techniques adopts the functional map framework, introduced in [29] and later extended significantly, e.g., in [20,32,35]. These methods work by establishing linear mappings between general real-valued functions and have been used to find related regions on shapes (see [30] for an overview).…”
Section: Generalized Shape Correspondencementioning
confidence: 99%
“…These techniques are better suited to the general shape correspondence problem, as they do not seek precise (e.g., bijective) maps between points, easily accommodating significant sampling, geometric, or even topological changes [35]. Furthermore, those soft maps can also be used as input to more refined point-based correspondence methods, to help improve the robustness and accuracy thereof [10].…”
Section: Introductionmentioning
confidence: 99%